Velvet retro : postsocialist nostalgia and the politics of heroism in Czech popular culture - Pehe, Veronika (Worlds of memory ;, 2020)
"Scholars of state socialism have frequently invoked "nostalgia" to identify an uncritical longing for the utopian ambitions and lived experience of the former Eastern Bloc. However, this concept seems insufficient to describe memory cultures in the Czech Republic and other contexts in which a "retro" fascination with the past has proven compatible with a steadfast critique of the state socialist era. This innovative study locates a distinctively retro aesthetic in Czech literature, film, and other cultural forms, enriching our understanding of not only the nation's memory culture, but also the ways in which popular culture can structure collective memory"--